Dissecting the Cytochrome P450 OleP Substrate Specificity: Evidence for a Preferential Substrate - Giacomo Parisi; Ida Freda; Cécile Exertier; Cristina Cecchetti; Elena Gugole; Gabriele Cerutti; Lucia D’Auria; Alberto Macone; Beatrice Vallone; Carmelinda Savino; Linda Celeste Montemiglio (Biomolecules, 2020)
The cytochrome P450 OleP catalyzes the epoxidation of aliphatic carbons on both the aglycone 8.8a-deoxyoleandolide (DEO) and the monoglycosylated L-olivosyl-8.8a-deoxyoleandolide (L-O-DEO) intermediates of oleandomycin biosynthesis. We investigated the substrate versatility of the enzyme. X-ray and equilibrium binding data show that the aglycone DEO loosely fits the OleP active site, triggering the closure that prepares it for catalysis only on a minor population of enzyme. The open-to-closed state transition allows solvent molecules to accumulate in a cavity that forms upon closure, mediating protein–substrate interactions. In silico docking of the monoglycosylated L-O-DEO in the closed OleP–DEO structure shows that the L-olivosyl moiety can be hosted in the same cavity, replacing solvent molecules and directly contacting structural elements involved in the transition. X-ray structures of aglycone-bound OleP in the presence of L-rhamnose confirm the cavity as a potential site for sugar binding. All considered, we propose L-O-DEO as the optimal substrate of OleP, the L-olivosyl moiety possibly representing the molecular wedge that triggers a more efficient structural response upon substrate binding, favoring and stabilizing the enzyme closure before catalysis. OleP substrate versatility is supported by structural solvent molecules that compensate for the absence of a glycosyl unit when the aglycone is bound.